Clinicopathological perspective on ovarian neoplasms in tertiary care hospital, Vijayapura - Zaryab Zaki; Afeeya Anjum Zari; Ashok M. Patil; Saeed M. Yendigeri (Al Ameen Medical College, 2019)
Background and Objective: Ovarian neoplasms are amongst the most common diseases affecting women in India which requires surgical remedy. This study aims to study prevalence of various ovarian neoplasms along with its correlation with various risk factors such as age, parity, distribution etc. The ultimate objective is to have a better understanding of these diseases and their risk factors resulting in effective prevention, better prognosis and ultimately a better life quality. Methods: This study was retrospective and prospective from January 2016 to December 2018. It was conducted on 106 patients who were diagnosed of ovarian cancers. Complete patient history was collected and analysed. Histopathological examination of the specimen was done and correlated with clinical records. Results: Ovarian neoplasms were most common in age group of 31 to 40 years. Benign neoplasms were much more common than malignant and borderline lesions. Surface epithelial tumors were much more common than germ cell tumors and sex cord stromal tumors. Most common presenting symptom was abdominal pain. Most of the lesions were cystic in consistency and were unilateral. Conclusion: Ovarian neoplasms are significant health concerns among middle aged women. Higher incidence is seen in nulliparous patients. Decreased incidence is seen in women with higher parity, lactation and oral contraceptive usage. Better understanding of risk factors helps in prevention of various ovarian cancers.